Pengaruh Beauty Vlogger Dan Citra Merek Terhadap Keputusan Pembelian Produk Kosmetik Emina Di Kota Malang (Studi Kasus Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2018) - Rizki Dewi Rahmawati; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine how the influence of Beauty Vlogger and Brand Image on Emina's Cosmetic Product Purchase Decision in Malang City. The population in this study were all students of the economics and business faculty of the Malang Islamic University class of 2018 who used Emina cosmetic products. The sample in this study were 85 female students. This study uses quantitative data and the method of collection is by using a questionnaire via google form and measured using a likert scale. The results of the study partially show that: 1) Beauty vlogger has a significant effect on purchasing decisions. 2) Brand image has a significant effect on purchasing decisions. All independent variables have a simultaneous effect on purchasing decisions. Keywords: Beauty Vlogger, Brand Image, Purchase Decision.